1983
DOI: 10.1002/micr.1920040406
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for end‐to‐end ureterostomy in the rat, using an indwelling reabsorbable stent

Abstract: The restoration of the continuity of the urinary tract represents one of the major problems in rat renal transplantation. End-to-end ureterostomy is the most physiologically effective technique; however, it involves noteworthy technical difficulties because of the extremely thin caliber of the ureter in the rat and the high incidence of postoperative hydronephrosis. We describe a new technique for end-to-end ureterostomy in the rat, where the use of an absorbable ureteral stent is recommended. A 5-0 plain catg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…As in our study, the use of the donor bladder cuff has facilitated restoration of the urinary tract continuity with ease of anastomosis. 13,14 In our experience, urine leak was encountered in one RT, which was associated with mortality. Native nephrectomy of the right kidney performed after 10 days of RT can provide the kidney time to recover from acute kidney injury.…”
Section: Discussionmentioning
confidence: 81%
“…As in our study, the use of the donor bladder cuff has facilitated restoration of the urinary tract continuity with ease of anastomosis. 13,14 In our experience, urine leak was encountered in one RT, which was associated with mortality. Native nephrectomy of the right kidney performed after 10 days of RT can provide the kidney time to recover from acute kidney injury.…”
Section: Discussionmentioning
confidence: 81%
“…42 Various microvascular techniques of arterial anastomosis have been described, including end-toend anastomosis between donor-to-recipient renal arteries (sutured, cuffed, or sleeved techniques), endto-side anastomosis between the donor recipient artery with an aortic patch to the recipient aorta, interposition of donor aortic segment with the renal artery between the transacted segment of recipient aorta, and end-to-side anastomosis between donor aortic conduit containing renal artery and the recipient aorta. 7,40,41,43,44 The presence of more than 1 renal artery, which is not uncommon, makes end-toend anastomosis impossible because of the narrow caliber and risk of thrombosis. 45 Karatazas and associates used donor aortic conduit attached to the renal artery and anastomosed end-to-side to the recipient abdominal aorta, which resulted in a survival rate of 87% at 15 days with no evidence of ischemic injury on histology.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving the testicular artery in the donor aortic stump helps to maintain blood supply of the ureter. 40 A wellorganized training program with a staged microvascular anastomosis skill development curriculum has been shown to be beneficial to the trainees. 9 We have reviewed the published literature on the surgical techniques of RT in the rat and have shown that there are several variations regarding vascular and ureteric anastomosis techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Right: The anastomosis was completed with interrupted sutures, after cannulation with a catgut thread (Carmignani et al, 1983). …”
mentioning
confidence: 99%